Zenobia : the curious book of business : a tale of triumph over yes-men, cynics, hedgers, and other corporate killjoys - Emmens, Matthew, 1951- (Berrett-Koehler Publishers, 2008)
Zenobia: a former industry giant that is bedeviled by paralyzing hierarchies, grossly inadequate communications, and distrust--is a broken place. Zenobia is a fortress doomed to collapse upon itself. Enter Moira, who has responded to a help wanted ad and seeks to find a given office, Room 133A. As she moves through the Zenobian maze, Moira makes some surprising discoveries about the power of teamwork, the role of the imagination, and the qualities that define true leaders. Her story is complemented and deepened by the story of a long-time Zenobia employee named Gallagher, the man who issued th.